2008
DOI: 10.1016/j.apsusc.2008.07.193
|View full text |Cite
|
Sign up to set email alerts
|

Comparative surface and nano-tribological characteristics of nanocomposite diamond-like carbon thin films doped by silver

Abstract: In this study we have deposited silver-containing hydrogenated and hydrogen-free diamondlike carbon (DLC) nanocomposite thin films by plasma immersion ion implantation-deposition methods. The surface and nano-tribological characteristics were studied by x-ray photoelectron spectroscopy (XPS), atomic force microscopy (AFM) and nano-scratching experiments. The silver doping was found to have no measurable effect on sp 2 -sp 3 hybridization of the hydrogenated DLC matrix and only a slight effect on the hydrogen-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(74 citation statements)
references
References 32 publications
5
69
0
Order By: Relevance
“…Obviously the absence of Ag peaks in the samples with Ag content below 13.1 at.% cannot exclude the presence of small Ag clusters with sizes below 2 nm, which are not detectable in XRD analysis. Silver carbides were neither expected nor observed and our results corroborate the studies on similar coating systems [15, 26,27,28]. In fact, previous studies of DLC coatings alloyed with silver indicated that the microstructure of these coatings was characterized as random dispersion of metallic Ag nanoparticles in an amorphous C-matrix [28,29].…”
Section: Chemical Composition and Microstructuresupporting
confidence: 89%
“…Obviously the absence of Ag peaks in the samples with Ag content below 13.1 at.% cannot exclude the presence of small Ag clusters with sizes below 2 nm, which are not detectable in XRD analysis. Silver carbides were neither expected nor observed and our results corroborate the studies on similar coating systems [15, 26,27,28]. In fact, previous studies of DLC coatings alloyed with silver indicated that the microstructure of these coatings was characterized as random dispersion of metallic Ag nanoparticles in an amorphous C-matrix [28,29].…”
Section: Chemical Composition and Microstructuresupporting
confidence: 89%
“…Moreover, as shown in Fig. 3, the curve-fitted C1s consists of four constituent peaks at binding energies of 282.9, 284.4, 285.2 and 286.58 eV, well corresponding to C-Si, sp 2 -C, sp 3 -C and C=O/C-O bonds [28,29]. XPS not only supports high fraction of sp2-C constituents in Si/GLC film, but also well gives the identification of the silicon-carbon bonding, and a small fraction of silicon carbide is believed to be presented in amorphous carbon matrix which is in good accordance with XRD analysis shown in Fig.…”
Section: Tribological Testmentioning
confidence: 98%
“…For instance, the performance of a-C can be tuned with the incorporation of transition metal in the material, such as Ag, Cu, or Ti nanoparticles: 11,[13][14][15][16][17][18][19][20][21] for metal-containing DLC, the carbon matrix provides high mechanical strength and the metallic inclusion enhances optical absorption. The structure and properties of the composite generally depend on the preparation technique and the deposition conditions, 6,8 which make the identification of universal structure-property relationships a challenging task.…”
Section: Introductionmentioning
confidence: 99%